2019
DOI: 10.3389/fncel.2019.00366
|View full text |Cite
|
Sign up to set email alerts
|

Role of C/EBP-β in Methamphetamine-Mediated Microglial Apoptosis

Abstract: Methamphetamine (MA) is a widely abused psychoactive drug that primarily damages the nervous system. However, the involvement of MA in the survival of microglia remains poorly understood. CCAAT-enhancer binding protein (C/EBP-β) is a transcription factor and an important regulator of cell apoptosis. Lipocalin2 (lcn2) is a known apoptosis inducer and is involved in many cell death processes. We hypothesized that C/EBP-β is involved in MA-induced lcn2-mediated microglial apoptosis. To test this hypothesis, we me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Lastly, new and emerging insightful scientific findings on METH-induced neuronal apoptosis have continually updated our understanding of its biomechanisms. For example, recent studies confirmed that CCAAT/enhancer-binding protein (C/EBP-β), Lipocalin2 (lcn2), and Sigma-1 receptor (σ-1R) might play an important role in METH-induced microglial apoptosis ( Shen et al, 2016 ; Chen et al, 2019 ). These new findings may provide new directions for future studies of natural agents and yield more refined and robust evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, new and emerging insightful scientific findings on METH-induced neuronal apoptosis have continually updated our understanding of its biomechanisms. For example, recent studies confirmed that CCAAT/enhancer-binding protein (C/EBP-β), Lipocalin2 (lcn2), and Sigma-1 receptor (σ-1R) might play an important role in METH-induced microglial apoptosis ( Shen et al, 2016 ; Chen et al, 2019 ). These new findings may provide new directions for future studies of natural agents and yield more refined and robust evidence.…”
Section: Discussionmentioning
confidence: 99%
“…So, MafB upregulation may be linked to the decrease of the inflammatory markers obtained in the 3-month-old transgenic mice. Relative to the downregulated genes, the C/EBP- β gene is, indeed, a direct target of miR-155 in this AD model [ 16 ], and its reduction is linked to a decrease in cell apoptosis [ 105 ] and delayed cell senescence [ 106 ]. On the other hand, the downregulation of Run2 , at both 3 and 9 months in the transgenic animals may lead to a reduction in microglia phagocytic ability [ 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lcn-2 can mediate apoptosis in microglia. For instance, in methamphetamine-induced striatal microglial apoptosis, the CCAAT-enhancer binding protein/Lcn-2 axis plays a critical role ( 97 ).…”
Section: Lcn-2 and Other Brain Cellsmentioning
confidence: 99%